Pengembangan Media Komik Berbasis Digital Terhadap Kemampuan Berpikir Kritis Siswa Pada Materi Metamorfosis Di Kelas Tinggi - Andayani, Feni; Maula, Luthfi Hamdani; Sutisnawati, Astri (STKIP Andi Matappa Pangkep, 2020)
This study aims to develop digital-based comic media on students' critical thinking skills on high-class metamorphosis material. This type of research uses Research and Development (RnD). The research instrument used questionnaires and tests. The subject of this research was conducted by a validator (a media expert lecturer, a material expert lecturer and 2 homeroom teachers). It can be concluded that the quality of comic products as a learning medium for critical thinking skills based on validation results by expert lecturers and practitioners. The final result of the comic media feasibility assessment on each component is that the content, material and media feasibility components are categorized as 'Excellent' by experts and practitioners, making it very feasible to test.